A Theoretical Approach To Journalist Education: THE İMPOTANCE OF VİSUAL LİTERACY AND BEİNG CRİTİCAL ABOUT CONSTRUCTİON THE RELATİON OF THE JOURNALİST WİTH SOCİAL ENGİNEERİNG - Hasbi ASLAN (Fırat University, 2019)
To overview the role about social engineering of journalist who is always valued and discussed its effect on potential of transformation and social exchange, by constructing the meaning in the society, to claim that they provide circulation can be implied in more polemical way as far as can be seen. However, constructing the meaning of transformation of journalism compherension that be able to pay attention to all kinds of knowledge relating to man in terms of formation, reading it, announcing it and in this context dealing with visual literacy and being critical in terms of the role of social engineering can be seen as an important need. In this essay, social engineering that predcits the claim about social engineering of journalist who designs the society by the way mentally design in written and visual platforms. In such a period that we take interaction with complex constructions in which are converted another production and consumption shape with meaningful constructions of the truth; the expected things that are hoped by the todays journalist who is in that position of post modern translator of scientific artistic social and current events; are a positive function of the social reflection shapes of the truth. Not for losing the mental truth in the production culture practical that are formed by the media,by considering that it is needed to effort for discovering the qualities that undertake as socially, the creativity contribution which a journalist formed on the cultural,mental,social and political order in the society is examined and also in this study; for a journalist it is considered that the problematic of contribution that is based on social truth and in deal with this truth ,reproduction and transmission of mentally constructions. That a journalist is a an important dynamic of social truth and mental platforms that journalist produced are considered important by the target mass are accepted as an important factor in terms of fixing our prevision.